CHALLENGES FACED BY TRAINEE TEACHERS AT IPGKPT IN TECHNICAL AND VOCATIONAL EDUCATION TRAINING (TVET) FOR SPECIAL NEEDS STUDENTS (Proceedings of International Conference on Special Education, 2023)
This study examine the challenges faced by trainee teachers at Institut Pendidikan Guru Kampus Pendidikan Teknik (IPGKPT) in providing Technical and Vocational Education Training (TVET) to students with special needs. A trainee teacher refers to an individual who enrolled in a teacher education program at IPGKPT. As trainee teachers, they are undergoing training to become a qualified teacher and typically required to complete a teacher training and internship as part of their program. The research aims to analyze the challenges faced by trainee teachers in teaching TVET for students with special needs from three aspects which are, professional development, competencies and skills, and attitudes and motivation of student teachers towards teaching TVET to students with special needs. By examining these three aspects, the researchers can provide a more in-depth understanding of the challenges and develop effective strategies for addressing them. The research design use in this study is the survey research design. The primary instrument for data collection was a questionnaire and the reliability of the questionnaire as certain using Cronbach’s Alpha test. In this context, TVET serves as a tool to help students with special needs acquire the necessary skills and knowledge to compete in the job market. Therefore, this research is expected to provide insights into how TVET teaching and learning can be tailored to the needs of students with special needs so that these challenges can be overcome by trainee teachers at IPGKPT. The findings of this research also could help trainee teachers and the education system to support students with special needs and improve the quality of education they receive.